Struktura moči kot izhodišče vadbe za moč - Strojnik, Vojko (Šport (Ljubljana), 2017)
The paper presents neuro-muscular function related to the structure of strength and power as motor ability which constitutes a basis for structuring the strength and power training methods. According to that, five major training goals are defined: improving of intra-muscular coordination (muscle activation level), increasing muscle mass, improving of intermuscular coordination during high-load action with isometric and concentric contraction, improving of inter-muscular coordination during high-load action with stretch-shortening cycle action, and improving strength endurance.
Keywords: cilji vadbe za moč; goals of strength; moč; neuro-muscular system; power training; sport; struktura moči; šport; živčno-mišični sistem